QRIS and Education : What Drives Students' Continuance Intention to Use It? - Nisa, Khairun; Budiman Abdulah; Maryani, Anie; R. Madhakomala (Agregat: Jurnal Ekonomi dan Bisnis, 2025)
This study investigates the factors influencing students' continuance use intention of QRIS at a university in Jakarta. The research aims to explore the role of digital financial literacy, perceived usefulness, perceived ease of use, and perceived security in shaping students' intention to continue using QRIS as a payment tool. A theoretical framework was developed based on the Technology Acceptance Model (TAM), integrating these constructs to form the model. Data from 205 respondents were collected and analyzed using Structural Equation Modeling (SEM). The results showed that perceived usefulness (β = 0.268, ρ < 0.05), perceived ease of use (β = 0.225, ρ < 0.001), and perceived security (β = 0.275, ρ < 0.005) significantly influenced students' continuance use intention. However, digital financial literacy (β = 0.069, ρ = 0.366) did not have a significant effect on continuance use intention. These findings contribute to the literature on digital payment adoption, emphasizing the importance of perceived usefulness, ease of use, and security in promoting the sustained use of QRIS among students. The study suggests that enhancing students' perceptions of these factors can drive greater acceptance and continued use of QRIS as a preferred payment method in the digital age.